Noninvasive prenatal screening for patients with high body mass index: Evaluating the impact of a customized whole genome sequencing workflow on sensitivity and residual risk. (20th December 2019) - Muzzey, Dale; Goldberg, James D.; Haverty, Carrie
Abstract: Objective: Women with high body mass index (BMI) tend to have reduced fetal fraction (FF) during cell‐free DNA‐based noninvasive prenatal screening (NIPS), causing test failure rates up to 24.3% and prompting guidelines that recommend aneuploidy screening other than NIPS for patients with significant obesity. Because alternatives to NIPS are only preferable if they perform better, we compared the respective sensitivities at different BMI levels of traditional aneuploidy screening and a customized whole‐genome sequencing NIPS. Method: The relationship between FF, aneuploidy, and BMI was quantified from 58 105 patients screened with a customized NIPS that does not fail samples because of low FF alone. Expected analytical sensitivity as a function of aneuploidy and BMI (eg, trisomy 18 sensitivity when BMI = 35) was determined by scaling the BMI‐ and aneuploidy‐specific FF distribution by the FF‐ and aneuploidy‐specific sensitivity calculated from empirically informed simulations. Results: Across all classes of obesity and assuming zero FF‐related test failures, analytical sensitivity for the investigated NIPS exceeded that of traditional aneuploidy screening for trisomies 13, 18, and 21. Conclusion: Relative to traditional aneuploidy screening, a customized NIPS with high accuracy at low FF and a low test‐failure rate is a superior screening option for women with high BMI. Abstract : What's already known about this topic? Women with high body mass index (BMI) often receive a test failure on noninvasive prenatal screening (NIPS) because of low fetal fraction (FF). The American College of Medical Genetics and Genomics recommends offering traditional aneuploidy screening to patients with "significant obesity." NIPS offerings differ in their efficacy at low FF. What does this study add? Irrespective of BMI and without FF‐based test failures, it is possible for a customized NIPS to provide all women with accurate prenatal screening.